Cancionero de música infantil didáctico con la utilización del programa musical Sibelius a los estudiantes de quinto y sexto semestre de la Carrera de Pedagogía de las Artes y las Humanidades, en el periodo mayo – octubre 2021 - Benítez Ferigra, Jefferson David (2022)
The purpose of this research is to provide to the future teachers with pedagogical and didactic resources that serve as a motivation for student´s learning and, at the same time, as a clear methodology to generate a meaningful teaching in students at different educational levels. It should be noted that in recent years in the academic sector it has been observed that teachers do not have the necessary tools to impart knowledge to children, which is why we believe it is appropriate to present our didactic children's music songbook, which uses technological tools, which allow to simulate the sounds that give the physical instruments through a digital system, these generate an excellent way to teach their students, within the same melodies are presented that refer to the daily life of people in order that students absorb knowledge in an entertaining and formative way. In this case we take into account the application of Sibelius musical notation, which allows us to create, transcribe and produce music with the aim of generating a more enriching learning where an active and cooperative intervention between the guided and their respective teachers will be encouraged, it is very necessary to constantly apply the instruction through this technique obtaining a valuable playful and participatory teaching.